2013
DOI: 10.1158/0008-5472.can-12-3979
|View full text |Cite
|
Sign up to set email alerts
|

Hsp27 Regulates Epithelial Mesenchymal Transition, Metastasis, and Circulating Tumor Cells in Prostate Cancer

Abstract: Defining the mechanisms underlying metastatic progression of prostate cancer may lead to insights into how to decrease morbidity and mortality in this disease. An important determinant of metastasis is epithelial-to-mesenchymal transition (EMT), and the mechanisms that control the process of EMT in cancer cells are still emerging. Here, we report that the molecular chaperone Hsp27 (HSPB1) drives EMT in prostate cancer, whereas its attenuation reverses EMT and decreases cell migration, invasion, and matrix meta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
162
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(167 citation statements)
references
References 41 publications
4
162
0
1
Order By: Relevance
“…EMT has been shown to play a fundamental role in metastasis. Intriguingly, HSPB1 mediates EMT, metastasis and circulating tumour cells in prostate cancer and breast cancer via modulation of STAT3/Twist signalling and nuclear factor-kappaB (NF-κB) respectively (Shiota et al 2013;Wei et al 2011). Endothelial to mesenchymal transition (EndMT) is another parameter known to be important for metastatic extravasation in brain endothelial cells and to promote invasiveness of infected endothelial cells, thus contributing to cancer progression (Gasperini et al 2012;Krizbai et al 2015).…”
Section: Shsps In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…EMT has been shown to play a fundamental role in metastasis. Intriguingly, HSPB1 mediates EMT, metastasis and circulating tumour cells in prostate cancer and breast cancer via modulation of STAT3/Twist signalling and nuclear factor-kappaB (NF-κB) respectively (Shiota et al 2013;Wei et al 2011). Endothelial to mesenchymal transition (EndMT) is another parameter known to be important for metastatic extravasation in brain endothelial cells and to promote invasiveness of infected endothelial cells, thus contributing to cancer progression (Gasperini et al 2012;Krizbai et al 2015).…”
Section: Shsps In Cancermentioning
confidence: 99%
“…OGX-427 is a secondgeneration antisense technology inhibitor that enables targeted downregulation of gene expression at the transcriptional level. It has been shown to potently reduce HSPB1 levels and in synergy with other cancer treatments to inhibit tumour growth, further validating these proteins as potential therapeutic targets for cancer treatment (Baylot et al 2011;Gleave and Monia 2005;Lamoureux et al 2014;Lelj-Garolla et al 2015;Shiota et al 2013). …”
Section: Shsps In Cancermentioning
confidence: 99%
“…Cell invasion assay was performed as described previously (Shiota et al 2013b). Briefly, cell invasion was performed using 8-mm pore matrigel invasion chambers (BD Biosciences).…”
Section: Cell Invasion Assaymentioning
confidence: 99%
“…Several strides have been carried out to identify the factors contributing to EMT in PCa. Transforming growth factor beta (Zhu & Kyprianou 2010), nicotinamide adenine dinucleotide-dependent histone deacetylase or SIRT1 (Byles et al 2012), platelet-derived growth factor (Kong et al 2009), TMPRSS2/ERG (Leshem et al 2011), SNAI2 (SLUG) (Emadi Baygi et al 2010), DAB2IP (Xie et al 2010), Hsp27 (HSPB1) (Shiota et al 2013), and miRNAs (Ru et al 2012) have all been identified as EMT regulators in PCa. Interestingly, the majority of these factors mediate EMT via zinc finger E-box-binding protein (ZEB) family members, such as ZEB1 (dEF1 or AREB6) and ZEB2 (Smad-interacting protein 1 (SIP1)) (Gregory et al 2011).…”
Section: Introductionmentioning
confidence: 99%